The relationship between intestinal Campylobacter species isolated from animals and humans as determined by BRENDA. - Kakoyiannis, C. K. (Cambridge University Press, 1988)
Intestinal thermophilic Campylobacter species produce stable patterns when subjected to bacterial restriction endonuclease DNA analysis (BRENDA); this technique is therefore of considerable value in epidemiological studies. BRENDA was used to examine thermophilic Campylobacter species from humans, wild and domestic animals. One hundred and ninety-four (61%) of 316 isolates of Campylobacter jejuni from humans had BRENDA patterns which could be matched to those of animal isolates. Poultry appear to be a major source of infection for C. jejuni in humans with nearly half (49.7%) of the human isolates giving patterns which were indistinguishable from those isolated from poultry. A total of 60 BRENDA types were identified from 316 human isolates and 11 of these had the same pattern as those isolated from poultry. One of the three Campylobacter coli BRENDA types recovered from poultry was indistinguishable from a human isolate type. Pigs appear to be only a minor source of C. coli infection for humans in New Zealand. Rats were found to be infected with strains of C. jejuni with BRENDA patterns indistinguishable from those infecting humans, poultry and a horse. None of the 102 isolates of Campylobacter species from wild birds gave BRENDA patterns similar to those of isolates from humans.